Empathy in Internal Medicine Residents at Community-based Hospitals: A Cross-sectional Study. (27th April 2018) - Foreback, Jami; Kusz, Halina; Lepisto, Brenda Lovegrove; Pawlaczyk, Barbara
Introduction: Many research reports revealed declining empathy in medical schools that continues in postgraduate years of training. Objective: The aim of this study is to examine the self-reported empathy levels of internal medicine (IM) residents in 3 community-based teaching hospitals. Methods: The Jefferson Scale of Physician Empathy, Health Professionals version, is an online, self-administered, questionnaire that was offered to 129 current and incoming residents at 1 osteopathic and 2 allopathic, IM training programs in Flint, Michigan. Results: Forty-five residents responded (35% response rate). Our residents' cumulative mean empathy score was 112.5 with a SD of 12.72, which is comparable with the cumulative empathy scores for IM residents at university hospitals. There was an increase in empathy score from the beginning level of training, postgraduate year 0 (PGY0), to the PGY1 level, and a noticeable, although statistically non-significant, decrease in empathy score for both PGY2 and PGY3 residents. The graduating residents' scores were higher compared with incoming residents. Conclusions: The cumulative mean empathy score in community-based IM residents showed an increase in the beginning of residents' training and decrease in empathy score by the end of training. There were significant differences in empathy scores by level of training at individual hospitals. This might be related to different targeted curricula.